Development of integrated Islamic mathematics modules based on high school students’ mathematical communication skills in probability - Delsi Ariani; Hayatun Nufus; Syarifah Syarifainy Syami (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2026)
This study employs a research and development (R&D) methodology based on the ADDIE model, comprising the analysis, design, development, implementation, and evaluation phases. The objective is to produce a mathematics module integrated with Islamic values, grounded in high school students’ mathematical communication skills, particularly regarding probability. The module aims to be valid, practical, and effective, and to enhance students’ knowledge of Islamic studies. The study was conducted at MAN 4 Kampar during the odd semester of 2025/2026, with 10th-grade students in Class X.A and experts as subjects, and the developed module as the object of study. The research design used was a pre-experimental one-shot case study. Data were collected through questionnaires, tests, and documentation, resulting in both quantitative and qualitative data. Data analysis included the Aiken index (validity), percentage (practicality), normality test, and one-sample t-test (effectiveness and Islamic knowledge). The data analysis showed that the module was highly valid (0.87) and highly practical (81.26% for small groups and 88.69% for limited groups). The posttest results were calculated using the left-tailed t-test, yielding. Therefore, it is accepted and rejected, indicating that students' average learning outcomes have reached the mastery level. Furthermore, the results of the Islamic knowledge questionnaire were analyzed using a right-tailed t-test, yielding. Therefore, it was rejected and accepted, indicating that students' average Islamic knowledge had increased. Based on these methods, it can be concluded that the integrated mathematics module grounded in Islamic values, which focuses on high school students’ mathematical communication skills in probability, demonstrates high validity, practicality, and effectiveness in the learning process and can enhance students’ religious knowledge.